A comparative study of impact behaviour between natural flax and glass FRP confined concrete composites. (30th April 2020) - Wang, Wenjie; Zhang, Xuejie; Mo, Zonglai; Chouw, Nawawi; Li, Zhongxian; Xu, Zhao-Dong
Highlights: Impact behaviour of flax and glass FRP confined concrete composites are compared. Damage mechanisms of the FFRP-PC and GFRP-PC composites are investigated. The confinement effectiveness of FFRP and GFRP confined plain concrete is compared. Strain rate effects on compressive strength and confinement effectiveness are investigated. Abstract: This research addresses the dynamic compressive properties of flax fibre reinforced polymer (FFRP) and glass fibre reinforced polymer (GFRP) confined concrete under impact loadings. The investigations were performed by conducting impact tests using a high-speed servo-hydraulic machine, with the impact-induced strain rates ranging from 0.2 s −1 to 30 s −1 . Plain concrete (PC), FFRP-PC, and GFRP-PC specimens were tested. The influences of FRP confinement and strain rate on compressive strength, stress and strain time histories were studied. The failure processes of the specimens were analysed via evaluating the high-speed camera photographs. The empirical relationship between the corresponding dynamic increase factor (DIF) of compressive strength and strain rate for PC, FFRP-PC and GFRP-PC were proposed based on experimental data. Experimental results of FFRP-PC and GFRP-PC specimens were compared to assess the confinement effectiveness of the FRP.